Swedish Alzheimer's disease variant perturbs activity of retrograde molecular motors and causes widespread derangement of axonal transport pathways - Feole, Monica; Pozo Devoto, Victorio M; Dragišić, Neda; Arnaiz, Cayetana; Bianchelli, Julieta; Texlová, Kateřina; Kovačovicova, Kristina; Novotny, Jan S; Havas, Daniel; Falzone, Tomas L; Stokin, Gorazd B (The Journal of biological chemistry, 2024)
Experimental studies in flies, mice, and humans suggest a significant role of impaired axonal transport in the pathogenesis of Alzheimer's disease (AD). The mechanisms underlying these impairments in axonal transport, however, remain poorly understood. Here we report that the Swedish familial AD mutation causes a standstill of the amyloid precursor protein (APP) in the axons at the expense of its reduced anterograde transport. The standstill reflects the perturbed directionality of the axonal transport of APP, which spends significantly more time traveling in the retrograde direction. This ineffective movement is accompanied by an enhanced association of dynactin-1 with APP, which suggests that reduced anterograde transport of APP is the result of enhanced activation of the retrograde molecular motor dynein by dynactin-1. The impact of the Swedish mutation on axonal transport is not limited to the APP vesicles since it also reverses the directionality of a subset of early endosomes, which become enlarged and aberrantly accumulate in distal locations. In addition, it also reduces the trafficking of lysosomes due to their less effective retrograde movement. Altogether, our experiments suggest a pivotal involvement of retrograde molecular motors and transport in the mechanisms underlying impaired axonal transport in AD and reveal significantly more widespread derangement of axonal transport pathways in the pathogenesis of AD.
Keywords: mutace; Animals; dyneiny; amyloidový prekurzorový protein beta; Lysosomes; axony; lyzozomy; dynaktinový komplex; Dyneins; lidé; Axons; Mice; Dynactin Complex; Mutation; myši; Genetic Variation; Endosomes; Alzheimer Disease; Alzheimerova nemoc; Amyloid beta-Protein Precursor; Axonal Transport; zvířata; genetická variace; axonální transport; endozomy; Humans